The Effect of the Principle of Confidentiality in Pre-Contract Negotiations - Ali, Waleed; Bin Saghir, Murad (Journal of Legal Sciences, 2026)
The aim of the research was to analyze the importance of privacy and confidential information in the negotiation processes of preliminary contracts, in order to understand the challenges and problems faced by the parties in maintaining their privacy and confidentiality of their information during the negotiation processes, the research relied on the comparative approach to study the legal principles and frameworks related to confidentiality in negotiating through various legislations, and through careful analysis, the research sought to provide recommendations to improve the legal framework and ensure a balance between the rights of the parties and ensuring confidentiality during the negotiation processes, and the research reached the following results: The legal bases for the obligation of confidentiality in contractual agreements varied according to the legal context and the existing system in each of them, as they were determined in the UAE by the intersection of Islamic law with the principles of civil law. The research also showed that confidentiality obligations included all information and data that one of the parties had access to during the negotiation process, such as prices, production plans and indirect means of advertising.